2018
DOI: 10.1016/j.jpeds.2017.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence of Sudden Unexpected Infant Death in the Newborn: 1995-2014

Abstract: The frequency of SUIDs during the neonatal period warrants ongoing attention to all circumstances contributing to this category of deaths. The development of a standardized definition of sudden unexpected postnatal collapse and a national registry of these events is recommended. Ongoing research on the effects of early neonatal practices on postneonatal SUID should also be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 30 publications
0
23
0
4
Order By: Relevance
“…Although SUID mortality has decreased overall in the United States since the mid-1990s, there has been little change in the number of deaths in the early neonatal period; thus, these deaths make up a larger percentage of total SUIDs. 5 The initial days of human life carry considerable risk, with death in the first week of life representing 73% of all deaths in the neonatal period (,28 days) worldwide. 6 Thus, this time window has been considered the most critical for a neonate.…”
mentioning
confidence: 99%
“…Although SUID mortality has decreased overall in the United States since the mid-1990s, there has been little change in the number of deaths in the early neonatal period; thus, these deaths make up a larger percentage of total SUIDs. 5 The initial days of human life carry considerable risk, with death in the first week of life representing 73% of all deaths in the neonatal period (,28 days) worldwide. 6 Thus, this time window has been considered the most critical for a neonate.…”
mentioning
confidence: 99%
“…We tested the association of SIDS with these two stressors using prevalence data from 16 worldwide populations, 15 countries, and over 40 US states. This is the first ecological link study to test the association between SIDS and MNC, and it is done at a time that SIDS rates remain alarmingly high [27] two decades after the "Back to Sleep" (BTS) campaign.…”
Section: Introductionmentioning
confidence: 99%
“…3 Of note, all five of the SUPC events occurred in the first 2 hours of postnatal life. 2 Bass et al 4 have shown that 29.2% of all neonatal cases occurred in the first week of postnatal life, which they defined as sudden unexpected infant death. 4 In some publications about SUPC, concern has been expressed about the safety of these newborn infants during their initial skin-to-skin and breastfeeding contacts with their exhausted, and in some cases, distracted mothers.…”
mentioning
confidence: 99%
“…2 Bass et al 4 have shown that 29.2% of all neonatal cases occurred in the first week of postnatal life, which they defined as sudden unexpected infant death. 4 In some publications about SUPC, concern has been expressed about the safety of these newborn infants during their initial skin-to-skin and breastfeeding contacts with their exhausted, and in some cases, distracted mothers. 1,2,4 Bass et al 5 have demonstrated an associated increase percent in SUPC rates in Baby Friendly Hospitals in Germany, the United Kingdom, and Sweden.…”
mentioning
confidence: 99%
See 1 more Smart Citation